High single-mode power conversion efficiency vertical-cavity top-surface-emitting lasers - Chalmers, S. A., author; Lear, Kevin L., author; IEEE, publisher (Colorado State University. Libraries, 1993)
We report advances in the power conversion (wall-plug) efficiency of vertical-cavity top-surface-emitting lasers. The devices were fabricated from molecular beam epitaxial layers using deep proton implants to define gain-guided lasers. The epitaxial structure included low resistance, piecewise linearly graded n-type and p-type mirrors, a triple In0.2Ga0.8As quantum-well active region, and a delta-doped contact layer. Power conversion efficiencies as high as 12.7% for continuous-wave single-mode operation were measured after several hours of device operation.
Keywords: laser cavity resonators; indium compounds; gallium arsenide; III-V semiconductors; laser modes; semiconductor lasers